2022
DOI: 10.3390/ijerph19063360
|View full text |Cite
|
Sign up to set email alerts
|

The Predictors of Psychological Well-Being in Lithuanian Adolescents after the Second Prolonged Lockdown Due to COVID-19 Pandemic

Abstract: Recent research highlights the impact of prolonged pandemics and lockdown on the mental health of youngsters. The second wave of COVID-19 brought an increase in mental health problems among young people. Therefore, this study aims to analyze the main factors arising from intra-individual, inter-individual, and environmental contexts that predict good psychological well-being in a group of adolescents after a second prolonged period of social restrictions and distance education. The study included 1483 school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
5
17
0
Order By: Relevance
“…It is known that female students exercise even less than male students [ 42 ]. Especially after the COVID-19 lockdown, it is known that lower physical activity is an important contributor to students’ poor well-being [ 51 ]. It is crucial to understand why PA habits of students are declining and also what is the motivation of those students that are regularly physically active.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that female students exercise even less than male students [ 42 ]. Especially after the COVID-19 lockdown, it is known that lower physical activity is an important contributor to students’ poor well-being [ 51 ]. It is crucial to understand why PA habits of students are declining and also what is the motivation of those students that are regularly physically active.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, infectious disease outbreaks have had a severe effect on mental health [ 2 , 3 ]. During the COVID-19 pandemic, social and sanitary measures, including quarantine and the widespread use of masks, were implemented in order to prevent viral transmission [ 4 , 5 , 6 ]. The large spread of the disease, the high mortality rate, and the encircling uncertainty caused severe psychological distress and have had a negative effect on society’s emotional wellbeing [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical symptoms of children infected with COVID-19 are milder than those of adults, and mortality is rare, studies showed that parents and children are especially vulnerable to feelings of emotional distress such as anger, depression, and irritability [ 2 ]. Many factors exacerbate their mental wellbeing, including quarantine, infection fear, frustration, and financial loss [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Many studies reported that teenagers were particularly affected, as quarantine caused a sudden interruption of all their social activities [ 6 , 7 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations